Appraisal System–Attitude as A Normative Compliance Device in Pandemic Communication: Realizing Authority Legitimacy through Positive Valuation - Dini Sri Istiningdias; Lia Maulia Indrayani; Eva Tuckyta Sari Sujatna; Wagiati (Universitas Ahmad Dahlan, 2026)
This study examines how positive valuation within the appraisal system–attitude operates as a normative compliance device in Indonesian public communication during the COVID-19 pandemic. Furthermore, this study used Systemic Functional Linguistics (SFL) especially appraisal and normative compliance theory. This study focuses on the statements delivered by government officials and broadcast through KompasTV streaming on YouTube. Meanwhile, this study employs a qualitative analytical approach using an abductive method, combining deductive procedures in data collection and analysis with inductive reasoning in presenting findings. The results of analysis showed 32 data as the most dominant appreciation-valuation as a part of appraisal systems-attitude device consisting of 30 realizations were positive and 2 were negative. Positive valuation was realized through four key variables, there are Sociality (3 data), Salience (7 data), Validity (9 data), and Maintenance (11 data). Across these variables, normative compliance and authority legitimacy were reinforced by emphasizing transparency, accuracy, consistency, credibility, and moral as well as social responsibility. Sociality highlighted the moral and social dimensions of authority, while salience underscored accuracy and credibility. Validity contributed to the perception of transparency and trustworthiness, and maintenance sustained compliance through consistent and credible communication. The predominance of positive valuation demonstrates that appraisal system-attitude, particularly appreciation, played a central role in legitimizing pandemic authority, fostering public trust, and ensuring adherence to communication protocols. By integrating Appraisal Theory with normative compliance frameworks, this study highlights the linguistic strategies through which governments construct legitimacy and reinforce authority during public health emergencies, offering insights into the role of language in shaping compliance and trust in times of crisis.